Evaluating social influence relations - Schwenk, Gero (Metodološki zvezki, 2009)
Subject of this paper is the measurement of social influence in social networks. The theoretical point of departure is twofold. First, focus is on cognitive processing of perceived influence. Second, three distinct dimensions of social influence are considered: persuasion, authority and coercion. Combining these considerations with Item Response Theory methods, questionnaire-type measurement instruments are proposed. These instruments are employed in a closed network case study where applicability is checked by means of network autocorrelation models.
Keywords: Družbena omrežja; Social networks; Measurement; Merjenje; družbeni vplivi; analiza omrežij